Angled manual traction and usual care for cervical radiculopathy: rationale and a protocol for a pilot randomized controlled trial (pAMTLER) - Liao, Shaojun; Huang, Junhan; Peng, Zhuolong; Hou, Yu; Su, Guoyi; Li, Yongjin; Wen, Zehuai; Lin, Dingkun (Frontiers in Medicine, 2025)
BackgroundAngled manual traction (AMT) is widely used for relieving moderate-to-severe cervicobrachial pain in patients with cervical radiculopathy (CR), yet its effectiveness has yet to be established by rigorous full randomized controlled trials (RCTs). We have designed an external pilot to evaluate the feasibility of a future large-scale, definitive RCT on AMT for CR.Methods48 CR participants with cervicobrachial pain (numeric rating scale ≥ 4) will be enrolled in a five-period pilot RCT and randomly assigned to receive either usual care alone or AMT plus usual care for 4 consecutive periods (each period defined as 7 days). The primary outcome will be feasibility, focusing on enrolment rate, retention rate, and protocol adherence. The secondary outcomes include pain in the cervicobrachial region, upper extremity numbness, muscle weakness, upper extremity and neck function, analgesic consumption (non-steroidal anti-inflammatory drugs and opiates), work ability, quality of life, emotional well-being prior to administering treatment at each period’s initial visit, as well as safety and intervention costs during the trial. We employ linear mixed-effect models on the efficacy-related outcome measures to assess the changes within and between groups over time, and determine the statistical trends of effectiveness.ResultsWe expect the trial to be completed by June 2026, with successful pilot targets defined as achieving ≥ 25% enrolment, ≥80% adherence, ≥80% retention, and superior health outcomes in the AMT add-on arm compared with usual care.ConclusionThis external pilot trial will provide robust data on feasibility and outcome variability for power calculations in the proposed future confirmatory RCT on AMT for CR. This pilot RCT will be invaluable to the design and management of the subsequent full-scale RCT.Trial registrationChinese Clinical Trial Registry (ChiCTR): https://www.chictr.org.cn/showproj.html?proj=236348 ChiCTR2400087289.